Poloxamer-based in situ gelling thermoresponsive systems for ocular drug delivery applications. Issue 8 (August 2019) - Soliman, Karim A.; Ullah, K; Shah, A.; Jones, David S.; Singh, Thakur R.R.
Highlights: Poloxamers-based in situ gels are potential vehicles for ocular drug delivery. Poloxamers possess reversible thermoresponsive gelling and mucoadhesive properties. Poloxamer can provide sustained release of both small and large drug molecules. Several technologies are used to control drug release from poloxamers-based gels. Abstract : In situ gels have recently received interest as ocular drug delivery vehicles because they combine the merits of easy instillation and sustained drug release. In this review, we focus on the use of poloxamers as in situ gelling systems in ocular drug delivery because of their thermoresponsive gelling behaviour, biocompatibility, and ease of sterilisation. Furthermore, the sol–gel transition temperature, mucoadhesive properties, and drug release profiles of poloxamer-based in situ gels can be finely tuned, enabling them to be used as vehicles for the delivery of small and large drug molecules to treat diseases of the anterior and posterior segments of the eye. Poloxamer-based ocular products have already found their way to the pharmaceutical market, but remain a potential arena for further investigation and commercial exploitation. Teaser: This article discusses advances in the use of poloxamers as in situ gels for ocular drug delivery, highlighting challenges, and recommending further possible applications.